Revitalizing E-waste: Eco-friendly electrochemical sensor for Hg(II) detection enhanced by oxygen vacancy in metal oxide nanostructures based on recycled LCD - Maroua Saadaoui (20090805) (2025)
In the current work, an innovative eco-friendly sensor using ceria integrated cobalt oxide nanosheets immobilized on LCD monitor (Ce@Co-EcoR) recycled from E-waste is presented. The Ce@Co-EcoR nanocomposite was thoroughly investigated using appropriate characterization techniques. This nanostructured electrode was employed to construct an electrochemical sensor to detect mercury. It showed a very low detection limit of 2.8 ppb, a wide detection ranges from 16 to 620 ppb, and a good sensitivity of 158.28 μA cm2.ppm−1. The sensor applicability was verified by performing interference, repeatability, stability studies. It was also applied to control the purity of sea water. This work underscores the potential of incorporating recycled materials onto sensor technology, not only to control environmental pollution, but also to promote sustainable practices in scientific innovation. Other Information Published in: Materials Today Sustainability License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.mtsust.2024.101015